Psalms Volume 1: Psalms 1-41 Psalms Volume 2: Psalms 42-89 Psalms Volume 3: Psalms 90-150, John Goldingay : book review - Mare, L. P. (Old Testament Essays, 2009)
The Baker Commentary on the Old Testament Wisdom and Psalms has proved itself in a very short time to be an excellent series. This three volume commentary on the Book of Psalms, written by John Goldingay, the David Allen Hubbard Professor of Old Testament at Fuller Theological Seminary in Pasadena, California, is no exception.
free